Use of ClassPoint and Interactive Applications as Ubiquitous Learning Media in Mufradat Learning: Literature Study - Nilam Cahya Munandar; Lidia Nelfianti; Rashid Rahman (International Journal of Language and Ubiquitous Learning, 2025)
Background. The rapid development of educational technology has shifted learning environments from traditional classroom settings toward flexible, technology-enhanced ecosystems that allow students to access materials anytime and anywhere. However, the integration of interactive platforms in Arabic vocabulary learning remains underexplored Purpose. This literature study aims to analyze how ClassPoint and selected interactive applications support ubiquitous learning principles, enhance student engagement, and improve vocabulary mastery. Method. The analysis indicates that ClassPoint, with its interactive quiz features, annotation tools, and immediate feedback system, contributes to active participation and fosters learner autonomy. Results. Similarly, other interactive applications such as Quizizz, Quizlet, and Kahoot facilitate repeated exposure to vocabulary, multimodal reinforcement, and context-based learning, all of which are essential for mufradat acquisition. The findings also show that ubiquitous learning environments provide greater flexibility for students to practice language skills beyond the classroom, thereby increasing retention and motivation. Conclusion. In conclusion, the literature supports the view that combining ClassPoint with interactive applications offers an effective and engaging approach to mufradat learning, particularly when aligned with ubiquitous learning principles.